DEVELOPMENT OF POLITICAL PARTIES AND PARTY FUNDING: MODELS AND CHARACTERISTICS - Hrvoje MATAKOVIC; Irena CAJNER MRAOVIC (CES Working Papers, 2015)
The first modern political parties were formed at the end of the 18th century and have, from those times up to now, undergone 4 developing phases; each of the phases is bound to ideal-type political party model: cadre parties, mass parties, catch-all parties and cartel parties. Each of these party models differentiates in various characteristics: party foundation, number of members, and way of leading the election campaigns, but also in ways of financing. This paper describes the above mentioned 4 phases of political parties’ development and 4 phases of parties' finances development; it will be analysed in detail positive and negative sides of each of the models of party financing.